A Case Report - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Fibrous Dysplasia is a fibro-osseous lesion characterized by the progressive replacement of normal bone by fibrous connective tissue resulting from arrest of bone maturation from woven bone to lamellar bone by a missense mutation. We report a 33-year old patient who presented with inability to open her of a month duration. On examination, patient had facial assymetry, anterior and posterior crossbite but scissors bite on the contralateral side, mouth deviation to the left on mouth opening associated with limited mouth opening, and there was no apparent swelling at the right preauricular region. The patient subsequently underwent surgery under general anesthesia following computed tomography (CT) scan. Fibrous dysplasia is a rare occurrence of the mandibular condyle, and its possibility in this location should be considered, pending a histopathologic report and the clinical importance of CT scan in the evaluation of temporomandibular joint lesions should be emphasized.